2016
DOI: 10.21714/1984-3925_2016v19n3a6
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica das republicações das demonstrações contábeis no período de 1997-2012

Abstract: RESUMOO objetivo do presente estudo foi analisar as características das republicações/refazimentos das demonstrações contábeis das empresas brasileiras listadas na BM&FBovespa, no período de 1997-2012. Este estudo, de natureza descritiva, documental, com abordagem quali-quanti, analisou dados de 5.608 demonstrações contábeis e relatórios de auditoria, utilizando, como estratégias, a análise de conteúdo e a estatística descritiva. Os resultados evidenciaram que, em média, 25% das demonstrações são republicadas;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
2
3
0
3
Order By: Relevance
“…Additionally, the benefit of restatement, might greater than the cost of doing so, as that might represent to the market that this specific large company is transparent. (Marques et al, 2016). This result corroborates that found by Marques et al (2017), which highlights that it does not mean that larger companies have more irregularities, but rather that, in Brazil, most restatement are the result of spontaneous acts.…”
Section: Results Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Additionally, the benefit of restatement, might greater than the cost of doing so, as that might represent to the market that this specific large company is transparent. (Marques et al, 2016). This result corroborates that found by Marques et al (2017), which highlights that it does not mean that larger companies have more irregularities, but rather that, in Brazil, most restatement are the result of spontaneous acts.…”
Section: Results Discussionsupporting
confidence: 90%
“…However, after using a proxy audit to control the auditor's endogenous choice, they found that clients of the Big Four auditors are less likely to report their earnings later than clients of auditors not in the Big Four. Antagonistic to the result found by Eshleman and Guo (2014), in Brazil, Marques et al (2016) identified that companies audited by the Big Four have a higher percentage of restatements.…”
Section: Main National and International Surveyssupporting
confidence: 51%
See 3 more Smart Citations